Uji Eksperimental Kuat Lentur Balok dan Pelat Beton Bertulang dengan Agregat Kasar dan Halus Beton Daur Ulang - Buen Sian; Adhijoso Tjondro; Riani Sidauruk; Sisi Nova Rizkiani (Research Report - Engineering Science, 2013)
In this experimental study, recycled concrete was used on cylinder specimens, the reinforcedconcrete beams, and the reinforced concrete slabs. Recycled concrete made of waste material fromlaboratory experiment is used for fine and coarse aggregates in this experiment. Cylinder specimens,beams, and slabs were used to determine the mechanical properties such as compressive strength,shear strength, split tensile strength, and flexural strength. Two mix designs with fc’ = 25 MPa andFc’ = 20 MPa were used in this study.Three different persentage variations of recycled concrete aggregates were used in mixdesign with ' c f = 20 MPa. Firstly, it consists of 100% recycled coarse aggregates (RCA) and 0%recycle fine aggregates (RFA). Secondly, it consists of 80% RCA and 20% RFA, and thirdly, it consistsof 60% RCA and 40% RFA. Nine reinforced concrete slabs with three variations of mix design weretested. The test results showed that the mechanical properties such as compressive strength, splittensile strength, shear strength, and flexural strength decreased when using more RFA. The flexuralstrength of reinforced concrete slab showed that the yield and ultimate moment are close to eachother, but ductility decreased when the RFA increased.Three different persentage variations of coarse recycled concrete aggregates (RCA) wereused in mix design with ' c f = 25 MPa, which are 0%, 50%, and 100% of RCA. The test results showedthe characteristics of compressive strength values are: fc’=28.7 MPa and fc’=28.4 MPa for each ofthe mixtures of 50% and 100% RCA. The split tensile strength values are: fct= 2.38 MPa, fct= 2.78MPa, and fct= 2.81 MPa for 0%, 50% and 100% RCA. While the shear strength are: Fv= 5,55 MPa, fv=4,28 MPa, and fv= 3.86 MPa for 0%, 50%, and 100% RCA.Keywords: recycled coarse aggregates, recycled fine aggregates, compressive strength, split tensilestrength, shear strength, flexural strength, ductility.